Intercontinental variations in the presentation and management of venous thromboembolism - Ochoa Chaar, Cassius Iyad; Chan, Shin Mei; Lee, Alfred I.; Bikdeli, Behnood; Tiberio, Gregorio; Chopard, Romain; Weinberg, Ido; Yamashita, Yugo; Nikandish, Reza; Monreal, Manuel (Journal of vascular surgery. Vascular insights (Online), 2025)
Venous thromboembolism (VTE) is a global disease with significant morbidity and mortality. However, variations in presentation and management of VTE between different continents have not been studied. This retrospective analysis of prospectively collected registry data compares presenting symptoms and treatment modalities of patients with VTE in three continents: Europe, America, and Asia. The data from the Registro Informatizado de la Enfermedad ThromboEmbólica registry (2011-2021) were reviewed. The Registro Informatizado de la Enfermedad ThromboEmbólica is the largest international registry dedicated to VTE that started in Spain and expanded worldwide. Patient characteristics and treatments were compared between Europe, America, and Asia using standardized differences. There were a total of 61,531 patients with VTE with the majority from Europe (90.3%), followed by Asia (6.3%) and America (3.3%). Patients diagnosed with VTE in America were significantly younger than the other continents. VTE patients in America were more likely to be Black and patients in Asia were more likely to have a lower body mass index when compared with patients from Europe and America. Patients with VTE in Asia presented with significantly more comorbidities including diabetes, coronary artery disease, and ischemic stroke. Also, patients from Asia were more likely to have recent major bleeding and active cancer. Conversely, patients from America had a significantly greater likelihood of having VTE related to travel. Anatomically, European patients were more likely to present with proximal DVT compared with patients from Asia and America. Patients in America were more likely to have low-risk pulmonary embolism (PE) and less likely to have intermediate-risk PE compared with patients from Europe and Asia. There was no difference in the proportion of patients with high-risk PE between continents. There was significant variation in the choice of initial and outpatient anticoagulation; vitamin K antagonists were more commonly used in Europe, whereas direct oral anticoagulants were more commonly used in America, and low-molecular-weight heparins were favored in Asia. Patients in Asia were less likely to receive systemic thrombolytic therapy. In terms of endovascular treatment, pharmacological thrombolysis was used more often for the treatment of PE in Europe compared with Asia and open pulmonary embolectomy was more common among American patients in the registry. There is significant intercontinental variation in VTE presentation and management. Future analyses should evaluate the relationship of these variations with clinical outcomes. Comparative research using a global registry could shed light on VTE biology and treatment.